Notes on Early Banking Schemes - Dunbar, Charles F. (Quarterly Journal of Economics, 1888)
Notes on Early Banking Schemes Get access Charles F. Dunbar Charles F. Dunbar Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 2, Issue 4, July 1888, Pages 482–490, https://doi.org/10.2307/1879392 Published: 01 July 1888